Of the Unit Ideas in the Sociology of Leisure - Zuzanek, Jiri (Anais Brasileiros de Estudos Turísticos, 2019)
Robert Nisbet, in The Sociological Tradition (1966), used the concept of unit-ideas in analyzing the sociological thought of the past and present. Unit-ideas are focal social concerns that generated and continue to invite conflicting interpretations, giving sociological thought its continuity and coherence. As examples of unit-ideas in the 19th century sociology, Nisbet listed alienation, the role of the community, relationship between the sacred and the secular. Several criteria need to be met, according to Nisbet, to qualify as unit-ideas. These ideas must have generality, be relevant to the present and the past, and be discernable in the works of the towering minds of an age. As well, unit-ideas must be specific for the given area of study and combine insight with observation (p. 5). In this article, an attempt will be made to apply Nisbet’s notion of unit-ideas to the historical study of leisure and labor, the two concepts that, in Bennett Berger’s words, “have sociological meaning only vis-à-vis each other.” (p. 28) Analysis of issues dominating the study of leisure and labor shows that discussion involving these phenomena centered historically upon several key and controversial issues such as: (1) the role of leisure and labor in forming human identity; (2) leisure and labor as stimuli of social change; (3) leisure’s and play’s role as sources of social stability; (4) leisure’s impact on the deepening or toning down of social inequalities; (5) division of labor and its alienating effects on leisure (spillover or compensation?); (6) future trends in the allocation of leisure time (will we live in a ‘society of leisure’ or of the ‘harried leisure class”?), and (7) leisure’s and labor’s contribution to subjective well-being (swb). While most of these issues fall predominantly into the domain of sociological inquiry, the interest in the relationship between leisure and swb is shared by sociology and social psychology. The first three unit-ideas (leisure as a source of human identity, social stability and a stimulus of change), have been examined in the literature mostly from the historical and anthropological perspectives. The conflicting views about the alienating effects of labor, the stratification implications of leisure, the direction of leisure trends, and the well-being corelates of leisure have been subject of conceptual discourse as well as empirical examination. My motivation for examining work-leisure relationships from the unit-ideas perspective is two-fold. I intend to show that these relationships are multifaceted and change with historical circumstances. I will refrain from the role of an arbiter, while discussing controversies surrounding the unit-ideas of leisure,’ and will leave their overall assessment to the concluding part of the article, showing there how these ideas reflect the “l’esprit du temps” (Zeitgeist), as well as ideological positioning of individual authors within it. In the concluding part, I will also address my second concern - the ‘partisan” or ‘lobbying’ position with regard to leisure often taken by leisure researchers. Leisure, to me, is a formidable challenge, but not necessarily a universal cure. The dividing line of the pros and the cons does not run between leisure and labor but within them. This is what this article will try to demonstrate.